El voleibol como estrategia en la mejora de la orientación espacial en estudiantes de la educación básica media - Barreiro Jiménez, Luis Enrique; Maldonado Quichimbo, Angie Isabel (Machala: Universidad Técnica de Machala, 2022)
The purpose of this research work was to determine the incidence of volleyball as a strategy for the improvement of spatial orientation in students of the secondary basic education sub-level, whose specific objectives were to review the literature, to define volleyball as a strategy for the improvement of spatial orientation in physical education classes, as well as field work, to identify the causes that limit the practice of volleyball and its contribution to the improvement of spatial orientation in physical education classes, and to the formulation of a proposal, which should guide the teacher responsible for the subject of physical education on the practice of volleyball to improve spatial orientation in students of the secondary basic education sub-level. The data collection was based on the qualitative approach with a descriptive methodology, achieving a diagnosis of the reality in the School of Basic Education Augusta Mora de Franco regarding volleyball starting from its history, its characteristics, technical fundamentals and basic regulations; likewise, spatial orientation integrated mainly by orientation, spatiality and spatial notions; and physical education with indicators such as the importance of physical education, sports practices, sport and school sport. The methods of greater incidence in this inquiry are the analytical-synthetic and others that were integrated as auxiliary, such as: the inductive-deductive, which contributed significantly at the time of collecting the information based on the specific objectives to contribute to the general objective, and were also written to cover aspects related to the literature review, with field research and finally to support the integrative proposal, as a contribution in favor of the educational institution that facilitated the access to carry out the research. In relation to the sample, 5 teachers of the middle school sub-level were considered, being those who showed the greatest predisposition to develop this research.
El presente trabajo de investigación tuvo como propósito, determinar la incidencia del voleibol como estrategia en el mejoramiento de la orientación espacial en estudiantes del subnivel de educación básica media, cuyos objetivos específicos se destinaron a la revisión bibliográfica; definir el voleibol como estrategia para el mejoramiento de la orientación espacial en las clases de educación física, de la misma forma al trabajo de campo, identificar las causas que limitan las prácticas del voleibol y su contribución en el mejoramiento de la orientación espacial en las clases de educación física, y al planteamiento de una propuesta, la misma que debe orientar al docente responsable de la asignatura de educación física sobre la práctica del voleibol para mejorar la orientación espacial en los estudiantes del subnivel de educación básica media. La recopilación de datos se fundamentó desde el enfoque cualitativo con una metodología de carácter descriptivo, logrando diagnosticar la realidad en la Escuela de Educación Básica Augusta Mora de Franco respecto al voleibol partiendo desde su historia, sus características, fundamentos técnicos y la reglamentación básica, así mismo, la orientación espacial integrada principalmente por la orientación, espacialidad y las nociones espaciales, y educación física con los indicadores como la importancia de la educación física, prácticas deportivas, deporte y deporte escolar. Los métodos de mayor incidencia en esta indagación son el analítico-sintético y otros que se integraron en calidad de auxiliares, como el inductivo-deductivo, mismos que aportaron significativamente al momento de recabar la información con base a los objetivos específicos para contribuir al objetivo general, y también estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación a la muestra se consideró a 5 docentes del subnivel básica media, siendo estos los que mostraron mayor predisposición para desarrollar esta investigación.
Keywords: VOLEIBOL; EDUCACION FISICA; ORIENTACION ESPACIAL; PROPUESTA METODOLOGICA